A Castilian agreement and two English briefs: writing in revolt in thirteenth-century Castile and England. Issue 1 (2nd January 2016) - Bjerke, Jillian M.
Abstract : This article compares the Barons' War against Henry III of England (1258–1265) and the revolt of the Castilian nobles against Alfonso X of Castile (1271–1273) and analyzes the ways the rebels opposed their kings in writing. It argues that the English barons and Castilian nobles viewed written authority and past custom as sufficient justification for their grievances and that they were aware of the political ramifications of their written statements. The English briefs submitted to Louis IX of France for arbitration in 1264 outlined the barons' grievances with Henry III. They appealed to past documents, such as Magna Carta and the Provisions of Oxford, and general consuetudines (customs) to support these grievances. They rarely attacked Henry III directly and forbore from naming themselves as they were still Henry's vassals. Similarly, the purported agreement between the Castilian nobles and Alfonso X, presented to Enrique I of Navarre in 1273, contained the nobles' demands of Alfonso. It emphasized the authority of previous regional fueros, both written and unwritten, and the customs of past kings. The Castilian nobles targeted Alfonso explicitly and named themselves with impunity, fearing little royal backlash. These under-studied documents offer a glimpse of the nobles' frustrations and preoccupations at specific moments in their revolts and highlight the importance of writing in rebellion.